Much Ado About (Scotland in) Europe. Issue 3 (August 2014) - Kenealy, Daniel
<x xml:space="preserve">Abstract</x> The issue of an independent Scotland's relationship with the European Union (EU) has been one of the most contentious and recurring issues of the referendum campaign. Discussion, to date, has been characterised by competing assertions from the two sides of the campaign. There has been little in the way of reasoned debate and consideration of the issue. Instead it has become grist to the mill of two campaign meta-narratives, one concerning the uncertainty inherent in a 'Yes' vote and the other concerning the continuity and stability that Scotland would enjoy following a 'Yes' vote. In this essay I will problematise the official position set out by the European Commission, clarify some of the outstanding issues, and raise questions about the proposed timescale for securing an independent Scotland's continuing membership of the EU. I argue that it would be in the interests of all parties, in the event of a 'Yes' vote, to avoid a scenario in which Scotland found itself outside of the EU and its legal framework for any period of time.